Identifikasi Kemandirian Belajar Peserta Didik Menggunakan E-Modul Berbantuan Liveworksheet Terintegrasi Potensi Lokal Toraja - Normalia Sandy Palumpun; Insih Wilujeng; I Gusti Putu Suryadarma; Suyanta Suyanta; Muhammad Hafizh Syaukani (Jurnal Penelitian Pendidikan IPA, 2022)
Self-regulated learning is a very important aspect of 21st-century learning. However, from the results of previous research and observations that have been made, it is known that the self-regulated learning of students is still in the low category. The purpose of this study was to analyze the self-regulated learning of students through the implementation of an e-module assisted by an integrated Liveworksheet to the local potential of Toraja in the interaction of living things with the environment. The type of research used is descriptive analysis, and the instrument used consists of a self-regulated learning questionnaire, interview guidelines, and observation sheets. The sample technique used was purposive sampling with 32 students of SMP Negeri 1 Rantepao as sample. The results showed that the aspect of don’t depend on other people had an average percentage is 62% (medium), an initiative is 65% (medium), discipline is 77% (high), the responsibility is 83% (high), self-confidence is 71% (high), setting study goals is 67% (medium), and evaluation is 71% (high). The overall average of students' self-regulated learning is in the high category, with a percentage is 70.85%. The use of learning media is very important in training students' self-regulated learning, so teachers are expected to be more innovative in using interactive learning resources